Difference between revisions of "009B Sample Final 1, Problem 2"

From Math Wiki
Jump to navigation Jump to search
(Created page with "<span class="exam"> We would like to evaluate :::::<math>\frac{d}{dx}\bigg(\int_{-1}^{x} \sin(t^2)2t\,dt\bigg).</math> <span class="exam">a) Compute <math style="vertical-ali...")
 
Line 2: Line 2:
 
:::::<math>\frac{d}{dx}\bigg(\int_{-1}^{x} \sin(t^2)2t\,dt\bigg).</math>
 
:::::<math>\frac{d}{dx}\bigg(\int_{-1}^{x} \sin(t^2)2t\,dt\bigg).</math>
  
<span class="exam">a) Compute <math style="vertical-align: -15px">f(x)=\int_{-1}^{x} \sin(t^2)2t\,dt</math>.
+
::<span class="exam">a) Compute <math style="vertical-align: -15px">f(x)=\int_{-1}^{x} \sin(t^2)2t\,dt.</math>
  
<span class="exam">b) Find <math style="vertical-align: -5px">f'(x)</math>.
+
::<span class="exam">b) Find <math style="vertical-align: -5px">f'(x).</math>
  
<span class="exam">c) State the Fundamental Theorem of Calculus.
+
::<span class="exam">c) State the Fundamental Theorem of Calculus.
  
<span class="exam">d) Use the Fundamental Theorem of Calculus to compute&thinsp; <math style="vertical-align: -15px">\frac{d}{dx}\bigg(\int_{-1}^{x} \sin(t^2)2t\,dt\bigg)</math> &thinsp;without first computing the integral.
+
::<span class="exam">d) Use the Fundamental Theorem of Calculus to compute&thinsp; <math style="vertical-align: -15px">\frac{d}{dx}\bigg(\int_{-1}^{x} \sin(t^2)2t\,dt\bigg)</math> &thinsp;without first computing the integral.
  
<span class="exam">d) Use the Fundamental Theorem of Calculus to compute&thinsp; <math style="vertical-align: -15px">\frac{d}{dx}\bigg(\int_{-1}^{x} \sin(t^2)2tdt\bigg)</math> &thinsp;without first computing the integral.
+
::<span class="exam">d) Use the Fundamental Theorem of Calculus to compute&thinsp; <math style="vertical-align: -15px">\frac{d}{dx}\bigg(\int_{-1}^{x} \sin(t^2)2tdt\bigg)</math> &thinsp;without first computing the integral.
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Foundations: &nbsp;  
 
!Foundations: &nbsp;  
 
|-
 
|-
|How would you integrate <math>\int e^{x^2}2x~dx</math>?
+
|How would you integrate <math>\int e^{x^2}2x~dx?</math>
 
|-
 
|-
 
|
 
|
::You could use <math style="vertical-align: -1px">u</math>-substitution. Let <math style="vertical-align: 0px">u=x^2</math>. Then, <math style="vertical-align: 0px">du=2xdx</math>.
+
::You could use <math style="vertical-align: -1px">u</math>-substitution. Let <math style="vertical-align: 0px">u=x^2.</math> Then, <math style="vertical-align: 0px">du=2xdx.</math>
 
|-
 
|-
 
|
 
|
::So, we get <math style="vertical-align: -14px">\int e^u~du=e^u+C=e^{x^2}+C</math>.
+
::So, we get <math style="vertical-align: -14px">\int e^u~du=e^u+C=e^{x^2}+C.</math>
 
|}
 
|}
  
Line 31: Line 31:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|We proceed using <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: 0px">u=t^2</math>. Then, <math style="vertical-align: 0px">du=2t\,dt</math>.
+
|We proceed using <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: 0px">u=t^2.</math> Then, <math style="vertical-align: 0px">du=2t\,dt.</math>
 
|-
 
|-
 
|Since this is a definite integral, we need to change the bounds of integration.  
 
|Since this is a definite integral, we need to change the bounds of integration.  
 
|-
 
|-
|Plugging our values into the equation <math style="vertical-align: 0px">u=t^2</math>, we get <math style="vertical-align: -5px">u_1=(-1)^2=1</math> and <math style="vertical-align: -3px">u_2=x^2</math>.
+
|Plugging our values into the equation <math style="vertical-align: -4px">u=t^2,</math> we get <math style="vertical-align: -5px">u_1=(-1)^2=1</math> and <math style="vertical-align: -3px">u_2=x^2.</math>
 
|}
 
|}
  
Line 61: Line 61:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|From part (a), we have <math style="vertical-align: -5px">f(x)=-\cos(x^2)+\cos(1)</math>.
+
|From part (a), we have <math style="vertical-align: -5px">f(x)=-\cos(x^2)+\cos(1).</math>
 
|}
 
|}
  
Line 67: Line 67:
 
!Step 2: &nbsp;
 
!Step 2: &nbsp;
 
|-
 
|-
|If we take the derivative, we get <math style="vertical-align: -5px">f'(x)=\sin(x^2)2x</math>, since <math style="vertical-align: -5px">\cos(1)</math> is just a constant.
+
|If we take the derivative, we get <math style="vertical-align: -5px">f'(x)=\sin(x^2)2x,</math> since <math style="vertical-align: -5px">\cos(1)</math> is just a constant.
 
|}
 
|}
  
Line 79: Line 79:
 
|'''<u>The Fundamental Theorem of Calculus, Part 1</u>'''
 
|'''<u>The Fundamental Theorem of Calculus, Part 1</u>'''
 
|-
 
|-
|&nbsp;&nbsp;Let <math>f</math> be continuous on <math style="vertical-align: -5px">[a,b]</math> and let <math style="vertical-align: -14px">F(x)=\int_a^x f(t)~dt</math>.
+
|
 +
:Let <math>f</math> be continuous on <math style="vertical-align: -5px">[a,b]</math> and let <math style="vertical-align: -14px">F(x)=\int_a^x f(t)~dt.</math>
 
|-
 
|-
|&nbsp;&nbsp;Then, <math style="vertical-align: 0px">F</math> is a differentiable function on <math style="vertical-align: -5px">(a,b)</math> and <math style="vertical-align: -5px">F'(x)=f(x)</math>.
+
|
 +
:Then, <math style="vertical-align: 0px">F</math> is a differentiable function on <math style="vertical-align: -5px">(a,b)</math> and <math style="vertical-align: -5px">F'(x)=f(x).</math>  
 
|}
 
|}
  
Line 89: Line 91:
 
|'''<u>The Fundamental Theorem of Calculus, Part 2</u>'''
 
|'''<u>The Fundamental Theorem of Calculus, Part 2</u>'''
 
|-
 
|-
|&nbsp;&nbsp;Let <math>f</math> be continuous on <math>[a,b]</math> and let <math style="vertical-align: 0px">F</math> be any antiderivative of <math>f</math>.
+
|
 +
:Let <math>f</math> be continuous on <math>[a,b]</math> and let <math style="vertical-align: 0px">F</math> be any antiderivative of <math>f.</math>
 
|-
 
|-
|&nbsp;&nbsp;Then, <math style="vertical-align: -14px">\int_a^b f(x)~dx=F(b)-F(a)</math>.
+
|
 +
:Then, <math style="vertical-align: -14px">\int_a^b f(x)~dx=F(b)-F(a).</math>
 
|}
 
|}
  

Revision as of 11:51, 18 April 2016

We would like to evaluate

a) Compute
b) Find
c) State the Fundamental Theorem of Calculus.
d) Use the Fundamental Theorem of Calculus to compute   without first computing the integral.
d) Use the Fundamental Theorem of Calculus to compute   without first computing the integral.
Foundations:  
How would you integrate
You could use -substitution. Let Then,
So, we get

Solution:

(a)

Step 1:  
We proceed using -substitution. Let Then,
Since this is a definite integral, we need to change the bounds of integration.
Plugging our values into the equation we get and
Step 2:  
So, we have


(b)

Step 1:  
From part (a), we have
Step 2:  
If we take the derivative, we get since is just a constant.

(c)

Step 1:  
The Fundamental Theorem of Calculus has two parts.
The Fundamental Theorem of Calculus, Part 1
Let be continuous on and let
Then, is a differentiable function on and
Step 2:  
The Fundamental Theorem of Calculus, Part 2
Let be continuous on and let be any antiderivative of
Then,
(d)  
By the Fundamental Theorem of Calculus, Part 1,
Final Answer:  
(a)  
(b)  
(c)  The Fundamental Theorem of Calculus, Part 1
  Let be continuous on and let .
  Then, is a differentiable function on and .
The Fundamental Theorem of Calculus, Part 2
  Let be continuous on and let be any antiderivative of .
  Then, .
(d)  

Return to Sample Exam